The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1177/147323000203000306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mandible as an Alternative Autogenous Bone Source for Oral and Maxillofacial Reconstruction

Abstract: The objective of this study was to quantify the amount of bone graft material present in the different regions of the mandible while avoiding the inferior alveolar neurovascular bundle, mental foramen and tooth injury. The study was carried out on 16 samples of dry, cadaverous skull. The dimensions of the anterior part of ascending ramus, mandibular symphysis and mandibular body in these samples were evaluated. The osteotomy lines in the anterior part of the ascending ramus were made in front of the mandibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…They also used calipers to measure the dimensions of the graft materials. The authors of the present study believe that their technique offers a more reliable evaluation of the graft volume for patients in clinical practice than that used in previous studies; it also avoids mental nerve or tooth injury, and simultaneously preserves the preoperative facial contour 6,15 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…They also used calipers to measure the dimensions of the graft materials. The authors of the present study believe that their technique offers a more reliable evaluation of the graft volume for patients in clinical practice than that used in previous studies; it also avoids mental nerve or tooth injury, and simultaneously preserves the preoperative facial contour 6,15 .…”
Section: Discussionmentioning
confidence: 93%
“…They harvested the symphysis bone graft as two roughly equivalent blocks and measured the average volume of the corticocancellous block as 4.71 ml in dentate human cadavers. GÜ NGÖ RMÜ S et al 6 conducted a study on a cadaverous skull, and although they reported the average vertical-horizontal lengths and thickness of the bone graft obtained from the mandibular symphysis, bone volume was not evaluated. They also used calipers to measure the dimensions of the graft materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To sum up, this untraditional denture design helps patient avoid occlusal pressing pain and get better denture retention [1][2][3].…”
Section: Discussionmentioning
confidence: 99%